Evaluation of the nutritional composition of quinoa (chenopodium quinoa willd) from the departments of Junín, Puno, Apurímac, Cusco and Ancash - Blanco Blasco, Teresa (2022)
The following study has as purpose giving knowledge about the chemical and nutritional content of the vhite quinua coming from the main areas of production of our country, as well as it diffuseness of its nutritional value inside the population, contributing to improve the level and quality of life of peruvians.For this study, it was taken 30 samples of white quinua coming from different mountain soils of Junín, Puno, Apurímac, Cusco y Ancash deparments (six samples for each one).They were obtained at random from the cultivated fields. The circunstances of this work was when the crop of this species was carried out and taken to the regional markets.We proceeded to the determination of the protein content by the method of Microkjeldhal, aminoacids content by liquid cromatography of high performance, Fat determination, carbohydrates, ash, fiber, humidity and temperature according to Peruvian technical norms, and determination of mineral by spectrometric in atomic absorption. This work was done in the Medicine Faculty of San Martín de Porres University. We obtained as conclusion that it exist significant differences in protein content according to the origin, we obtained the highest value average in Junín, 13,71%, the same situation happened with the minerals, being the highest value averae the magnesium with 299 mg/100g of quinua, that covers 95% of the daily requiremente for an adult. The highest value averages of Iron were in Cusco with 8,21 mg/100 g of food, that covers 80% of the daily requirements for an adult. The highest value averages for copper were in Junín with 1, 16mg/100 g that covers 78% of the daily requirements for an adult which are from 1,5 to 3 mg.In relation to aminoacids, it exist significant differences between the lysine content in Junín which was 5,8% of protein and in Ancash which was 6,81 % of protein, in this case 100g of quinua would cover 82% and 92% of its daily requirements respectively. In the case of the threonine its values varied between 3,49% of protein in Cusco and 5.38% of protein in Ancash, being its differences statiscally significant in the same area of origin, it covers from 73% to 130% of the daily requirements of this aminoacid in an adult respectively.Acording to the methionine its values varied from 1,98% of protein of quinua in Junín and 2,69% of protein in Ancash, its values have statistic significance according to the same area of origin, this would cover from 27% to 34% of its daily Methionine requirements in an adult respectivley.We reached the conclusion that the quinua presented better levels of concentration in proteins in Junín, probably for the kind of crop used in the area, where pesticides are applied besides urea, the kind of soil, the kind of rotation applied in the area and also the environmental conditions of its production.In relation with minerals we could mention the concentration of magnesium and copper that would be related to the capacity that this plant has for capturing these minerals as well as the composition of the soil in the area of origin.I Puno our grain presented the lowest level of protein beig related with the kind of crop used at Titicaca lake, it uses only natural ferti1izer, they are extensive plantation only to sow quinua, that is why it is not possible that the soil enrich with Nitrogen.In Ancash the levels of lysine, methionine threonine and valine were the highest found. We know that in this area it is used to practicing the alternate crop with beans or potatoes, besides being a natural and unirrigated valley, which it gives characteristics of different crops.The quinua es nutritioanally very rich, specially in aminoacids that it would cover many of the requirements in the adolescents and adults, but not for the babies in process of lactation and school students, this would be a complement in their diet.